The Effectiveness of Simulation Methods on Prospective Teachers’ Professionalism in Science Learning - Muhamad Jalil (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2018)
Professionalism in teaching is needed in the Curriculum 2013. As many as 54% of the 68 students stated not yet familiar with the scientific approach. The average value of didactic concept mastery is 55 under the minimum completion criteria. The objectives of this research are to (1) test the effectiveness of the application of simulation methods on the professionalism of prospective teachers; and (2) analyze student responses. The research design is Posttest Only with Non-Equivalent Control Group Design. Data of the simulation method was analyzed by a descriptive method. One sample t-test is used to know the achievement of the average mastery of pedagogic competence. The Independent t-test was addressed to know whether the average value of professional competence of the experimental class is higher than the control class. The response was analyzed by Likert scale. The result of the research shows that: (1) the simulation method of science learning on the professionalism of prospective teachers in IAIN Kudus is effective; and (2) Student response to the positive simulation method is 79,00% from 31 students.